(untitled) (Journal of Global Humanities and Social Sciences, 2023)
In this new era, the economic globalization and rapid development of science and technology are calling an innovation of college English teaching in higher education. Based on the study on the teaching designs in FLTRP Star Teacher Contest and papers relating to college English teaching innovation, this paper is trying to find useful strategies for the innovative teaching design of college English curricula, hoping to make a contribution to the exploration of English teaching innovation in higher education.